2008
DOI: 10.1073/pnas.0710032105
|View full text |Cite
|
Sign up to set email alerts
|

Soft glassy rheology of supercooled molecular liquids

Abstract: We probe the mechanical response of two supercooled liquids, glycerol and ortho-terphenyl, by conducting rheological experiments at very weak stresses. We find a complex fluid behavior suggesting the gradual emergence of an extended, delicate solidlike network in both materials in the supercooled state-i.e., above the glass transition. This network stiffens as it ages, and very early in this process it already extends over macroscopic distances, conferring all well known features of soft glassy rheology (yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 38 publications
8
78
0
4
Order By: Relevance
“…The first is a Couette geometry (Anton Paar CC 20) similar in dimensions to that used in Zondervan's study: 2 The gap size between inner and outer cylinder is 1 mm. The inner cylinder has a radius of 10 mm and is 30.1 mm long, with a conical bottom.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first is a Couette geometry (Anton Paar CC 20) similar in dimensions to that used in Zondervan's study: 2 The gap size between inner and outer cylinder is 1 mm. The inner cylinder has a radius of 10 mm and is 30.1 mm long, with a conical bottom.…”
Section: Methodsmentioning
confidence: 99%
“…1 Most strikingly, the observed lifetime of the spatial heterogeneity is on the order of hours, about 6 orders of magnitude longer than the typical time for a glycerol molecule to reorient. Moreover, a recent experiment by Zondervan et al 2 has shown that the rheology of supercooled glycerol near the glass transition exhibits a novel viscoelastic behavior after sufficient aging of the sample. This was a surprising finding, given that supercooled liquids are thought to be pure Newtonian liquids whose viscosity diverges at the glass transition temperature T g .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These materials exhibit distinctly non-liquid-like features, a soft glassy rheology, which make them very attractive for technological applications and intriguing systems in terms of physics of condensed matter [8,9]. Indeed, several technical applications take advantage of GC physico-chemical properties.…”
Section: Introductionmentioning
confidence: 99%